Regional Inequality Based on Infrastructure Indicators Using Principal Component Analysis (PCA) - Kikin Windhani; Fajar Hardoyono (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2017)
This research aimed to identify the development gap among 27 sub-districts in Banyumas Regency based on infrastructure indicators using Principal Component Analysis (PCA). The infrastructure indicators used were the quality of road, lighting, transportation, market, bridges and schools. The data were collected by observation in 27 sub-districts of Banyumas Regency. From the analysis result with PCA, it can be determined that based on infrastructure indicators, the sub-districts in Banyumas Regency were divided into 4 clusters, namely: Cluster I with 1 sub-district; Cluster II with 3 sub-districts; Cluster III with 3 sub-districts, and the remainining 20 sub-districts were in Cluster IV.Keywords: Gap, Infrastructure, Principal Component Analysis (PCA).